The Effect of Debt to Asset Ratio, Return on Equity, and Current Ratio on Stock Prices of Pharmaceutical Companies Listed on the Indonesia Stock Exchange 2016-2019 Period - Ade Onny Siagian; Hadion Wijoyo; Yoyok Cahyono (Journal of World Conference (JWC), 2021)
This research aims to determine: The influence of Current Ratio (CR), Debt to Asset Ratio (DAR), and Return on Equity (ROE) either partially or simultaneously on Stock Price of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) 2016-2019 period. Data were taken from the Indonesia Stock Exchange (IDX) website. Analysis prerequisite test including normality test, multicollinearity, heteroscedasticity, and autocorrelation. Data analysis technique used is multiple linear regression analysis. Statistical results also show that the current ratio (X1) and return on equity (X3) partially have a positive and significant effect on stock prices (Y). Debt to asset ratio (X2) partially does not have a significant effect on stock prices (Y). Simultaneously current ratio (X1), debt to asset ratio (X2), and return on equity (X3) have a positive and significant effect on stock prices (Y).